Influence of Social Network Strength on Entrepreneurial Opportunity Recognition: A Chain Mediation Model of Need Knowledge and Technological Knowledge - Jing Fan (Hindawi Limited, 2021)
Entrepreneurial opportunity recognition is a key focus of entrepreneurship research and has received considerable attention in recent years. Previous research has highlighted that social network strength, need knowledge, and technological knowledge are important factors in entrepreneurial opportunity recognition and that these factors in isolation cannot sufficiently explain how entrepreneurial opportunities are recognized. Nonetheless, little is known about the effect that social network strength may exert on entrepreneurial opportunity recognition through need knowledge and technological knowledge. Building on social network theory, this study develops and examines a chain mediation model that incorporates need knowledge and technological knowledge into the relationship between social network strength and entrepreneurial opportunity recognition. The results of this study demonstrate that the effect of social network strength on entrepreneurial opportunity recognition can be partitioned into the direct and indirect effects. In particular, the effect of social network strength on entrepreneurial opportunity recognition is mediated by need knowledge, not by technological knowledge. Moreover, need knowledge and technological knowledge play a continuous mediating role in the relationship between social network strength and entrepreneurial opportunity recognition. These findings extend the entrepreneurial opportunity recognition literature by casting light on the knowledge conduits linking social network strength to entrepreneurial opportunity recognition.